High-Involvement Human Resource Practices, Inclusive Leadership And Adaptive Performance Among Head Nurses Of Private Hospitals In Jordan - Enaizan Bataineh, Mohammad Saleh (2020)
Reducing adaptive performance affects productivity as well as an organisation’s efficiency. This study investigates the impact of recognition practices, empowerment practices, competence development practices, fair rewards practices, information-sharing practices, and inclusive leadership on the adaptive performance of private hospitals in Jordan. It then evaluates the mediating effect of individual innovative behaviour between the relationships of recognition practices, empowerment practices, competence development practices, fair rewards practices, information-sharing practices, inclusive leadership and adaptive performance. The theoretical framework developed for this study is based on the Social Exchange Theory and Job Demands-Resources Theory. The sample comprised 169 head nurses from private hospitals in the capital city Amman. The data was then analysed using Smart PLS version 3.2.8 and SPSS version 25. The results showed significant positive relationships between recognition practices and inclusive leadership towards individual innovative behaviour, and between individual innovative behaviour and adaptive performance, while there emerged a significant negative relationship between fair rewards practices towards individual innovative behaviour.